Ab-initio analysis of magnetic, structural, electronic and thermodynamic properties of the Ba2TiMnO6 manganite (2018)
Perovskite-like materials, which include magnetic elements, have relevance because their technological perspectives of applications in the spintronics industry. In this work, the magnetic, structural, electronic and thermodynamic properties of the Ba2TiMnO6 of the perovskite-like manganite are investigated. Calculations are carried out through the Full-Potential Linear Augmented Plane Wave method (FP-LAPW) within the framework of the Density Functional Theory (DFT) with exchange and correlation effects in the Generalized Gradient (GGA) and Local Density (LDA) approximations, including spin polarization. From the minimization of energy as a function of volume using the Murnaghan’s state equation the equilibrium lattice parameter and cohesive properties of this compound were obtained. The study of the electronic structure was based in the analysis of the electronic density of states (DOS), and the band structure, showing that this compound evidences an effective magneticmoment of 3.0 μB. The pressure and temperature dependence of specific heat, entropy, thermal expansion coefficient, Debye temperature and Grüneisen parameter were calculated by DFT from the state equation using the quasi-harmonic model of Debye. A specific heat behavior CV≈CP was found at temperatures below T = 400 K, with Dulong-Petit limit values, which are quite higher than those, reported for simple perovskites.